Estimation of Oceanic and Land Carbon Sinks Based on the Most Recent Oxygen Budget. Issue 7 (12th July 2021) - Li, Changyu; Huang, Jianping; Ding, Lei; Liu, Xiaoyue; Han, Dongliang; Huang, Jiping
Abstract: Robust assessments of global carbon uptake are important for understanding Earth's carbon cycle and its response to human impacts. Here, based on the most recent oxygen budget, we presented an alternative estimate of ocean and land carbon sinks over the past few decades and future projections under climate change. For the period from 1990 to 2015, the ocean and land carbon sinks were ∼2.16 ± 0.73 and 1.37 ± 0.91 GtC/yr, respectively, which are in good agreement with the results from the Global Carbon Project (GCP). Our estimated temporal evolution of oceanic carbon uptake, however, presents a stronger decadal variation than the quasi‐monotonous increase estimated by the GCP. Future projections of carbon sinks show significant discrepancies under different scenarios. At the end of this century, the ocean and land sinks will be 2.96 and 0.75 GtC/yr, respectively, under RCP4.5 (representative concentration pathways), while these values will be much larger under RCP8.5 at ∼5.70 and 3.69 GtC/yr, highlighting the vital role of the human‐induced influence on the carbon cycle. Plain Language Summary: In the Earth system, the ocean and land work as the carbon reservoirs (i.e., the CO2 sinks) to absorb CO2 emissions from human activities, helping to buffer climate change greatly. In this study, the land and ocean sinks are estimated using the most recent oxygen budget. We presented the evolution of the carbon sink in the last few decades as well as its changes under different warming scenarios in the future. Our results reveal the combinations of natural and anthropogenic effects on oceanic carbon sink in the historical period. Furthermore, the vast differences under two warming scenarios indicate the importance of human efforts on emission‐reduction. Key Points: Based on the oxygen budget, this study estimated the land and ocean carbon sinks and its response to climate change Estimations reveal decadal variability of ocean carbon sink due to combinations of effects of anthropogenic forcing and natural variability Future projections indicate the vital role of human activities on changes of ocean and land carbon sink